Hubungan Edukasi Proses Penyembuhan Luka dengan Level Ansietas terhadap Pasien Pasca Operasi Debridement - Saherna, Jenny; Olviani, Yurida; Hadrianti, Dessy; Rianty, Dewi (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Education about the wound healing process is the main component of basic nursing intervention in helping to reduce anxiety levels in post-operative debridement, in this case, it is necessary to evaluate the patient’s understanding in receiving the information that has been conveyed by the nurse, so that the goal of reducing anxiety levels can be realized. Anxiety is one of the triggers for instability of vital signs which has an impact on the wound healing phase. The aim of the research was to look at the relationship between education on the wound healing process and the level of anxiety in patients after debridement surgery. This research is quantitative, non experimental, using cross-sectional with purposive sampling method and spearman rank correlation test analysis, a total of 73 respondents with data collection through questionnaires. The result showednthat respondents with no anxiety were 1 person (1.4%), mild anxiety were 17 people (23.3%), moderate anxiety were 42 people (57.5%), severe anxiety were 10 people (13.7%), very severe anxiety as many as 3 people (4.1%). The conclusion resulting from data analysis was asymp. Sig. (2-Tiled) P = 0.007, P < 0.005, there is a significant relationship between understanding and anxiety level in post-operative debridement patients.    Keywords: Education, Wound Healing, Anxiety, Post-Operative Debridement  ABSTRAK Edukasi tentang proses penyembuhan luka merupakan komponen utama dasar intervensi keperawatan dalam membantu penurunan level ansietas pada pasien pasca operasi debridement, dalam hal ini diperlukan evaluasi pemahaman pasien dalam menerima informasi yang telah disampaikan oleh perawat, agar tujuan penurunan level anisetas dapat terealisasi. Ansietas salah satu pemicu ketidakstabilan tanda-tanda vital yang berdampak terhadap fase penyembuhan luka. Tujuan penelitan melihat hubungan edukasi proses penyembuhan luka dengan level ansietas terhadap pasien pasca operasi debridement. Penelitian ini kuantitatif, jenis non eksperimental, menggunakan cross-secstional dengan metode purposive sampling dan analisis uji korelasi spearman rank, total 73 responden dengan pengumpulan data melalui kuesioner. Hasil penelitian responden dengan tidak ada ansietas sebanyak 1 orang (1,4%), ansietas ringan sebanyak 17 orang (23,3%), ansietas sedang sebanyak 42 orang (57,5%), ansietas berat sebanyak 10 orang (13,7%), ansietas berat sekali sebanyak 3 orang (4,1%).        Kesimpulan penelitian hasil analisis data didapatkan hasil Asymp. Sig. (2-Tailed) p = 0.007, p < 0.05, ada hubungan signifikan antara pemahaman dengan level ansietas pada pasien pasca operasi debridement. Kata Kunci: Edukasi, Penyembuhan Luka, Ansietas, Pasca Operasi Debridement